2019
DOI: 10.1039/c9ra08065a
|View full text |Cite
|
Sign up to set email alerts
|

A high-sensitive room temperature gas sensor based on cobalt phthalocyanines and reduced graphene oxide nanohybrids for the ppb-levels of ammonia detection

Abstract: Highly sensitive gas sensing materials are of great importance for environmental pollution monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 48 publications
0
15
1
Order By: Relevance
“…To enhance the organic heterojunction effects, new and emerging organic nanomaterials such as graphene or its oxides should be associated with MPc. A few such studies have been reported in recent researches involving CuPc/reduced graphene oxide and CoPc/reduced graphene oxide [ 80 , 81 ]. The NH 3 sensing properties of chemiresistors based on these hybrid materials have shown improvements, demonstrated by experimental detection of 200 ppb of NH 3 and long operation stability.…”
Section: Discussionmentioning
confidence: 99%
“…To enhance the organic heterojunction effects, new and emerging organic nanomaterials such as graphene or its oxides should be associated with MPc. A few such studies have been reported in recent researches involving CuPc/reduced graphene oxide and CoPc/reduced graphene oxide [ 80 , 81 ]. The NH 3 sensing properties of chemiresistors based on these hybrid materials have shown improvements, demonstrated by experimental detection of 200 ppb of NH 3 and long operation stability.…”
Section: Discussionmentioning
confidence: 99%
“…The integration of sensors into portable devices requires the creation of devices based on carbon nanomaterials with a high surface area, such as carbon nanotubes [ 23 , 89 ], graphene oxide [ 90 , 91 ], graphite oxide [ 92 ], reduced graphene oxide [ 93 , 94 , 95 ], nanoporous carbons [ 96 , 97 , 98 ], fluorinated graphene [ 99 , 100 , 101 ], aerographite [ 102 , 103 ], etc. Initially, the majority of the research was based on the creation of flexible films for the detection of aggressive gases, including ammonia.…”
Section: Ammonia Gas Sensors and Gas Sensing Mechanismmentioning
confidence: 99%
“…After adsorption, the ease of charge transfer between 3-CuPc derivatives and rGO results in the relatively large sensitivity of such sensors. Guo et al 19 explored gas sensing performance of four nanohybrid materials synthesized based on rGO and Co phthalocyanines (CoPc) containing different phenoxyl substituents (cpoCoPc, poCoPc, cmpoCoPc, and mpoCoPc). After the nanohybrid synthesis, solutions of the Pcs/rGO were dropped on gold interdigitated electrodes using a microsyringe, as shown in Figure 5 a. UV–vis spectroscopy found that the interaction between rGO and Pcs leads to reduction in the HOMO–LUMO energy gap of the phthalocyanines.…”
Section: Hybrids Based On Reduced Graphene Oxide/metallophthalocyaninmentioning
confidence: 99%
“…(b) Response of PcCos, rGO, and PcCo/rGO hybrid-based sensors to 100 ppm of NH 3 and 5000 ppm of other gases. Adapted with permission from ref ( 19 ). Copyright 2019, Royal Society of Chemistry.…”
Section: Hybrids Based On Reduced Graphene Oxide/metallophthalocyaninmentioning
confidence: 99%